2009
DOI: 10.1002/cne.22041
|View full text |Cite
|
Sign up to set email alerts
|

3D electron microscopic reconstruction of segments of rat cerebellar purkinje cell dendrites receiving ascending and parallel fiber granule cell synaptic inputs

Abstract: Growing physiological evidence suggests that there are functional differences between synapses made by the ascending and parallel fiber segments of the granule axon on cerebellar Purkinje cells. Supporting this view, our previous electron microscopic studies suggested that these synapses also contacted different regions of the Purkinje cell dendrite, and in particular that ascending segment synapses are made exclusively on the smallest diameter Purkinje cell dendrites. In the current study we used serial elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 47 publications
(9 reference statements)
0
43
0
Order By: Relevance
“…Parallel fiber and ascending inputs have received much attention because of the consequences that their relative weights may have for information processing by the circuitry of the cerebellar cortex (Llinas, 1982; Barbour, 1993; Isope and Barbour, 2002; Santamaria et al, 2002; Santamaria and Bower, 2005; Sims and Hartell, 2005, 2006; Marcaggi and Attwell, 2007; Lu et al, 2009). If the weight of an ascending input is severalfold larger than that of a parallel fiber input, then the ascending input could play a differential role in relaying information to Purkinje cells.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel fiber and ascending inputs have received much attention because of the consequences that their relative weights may have for information processing by the circuitry of the cerebellar cortex (Llinas, 1982; Barbour, 1993; Isope and Barbour, 2002; Santamaria et al, 2002; Santamaria and Bower, 2005; Sims and Hartell, 2005, 2006; Marcaggi and Attwell, 2007; Lu et al, 2009). If the weight of an ascending input is severalfold larger than that of a parallel fiber input, then the ascending input could play a differential role in relaying information to Purkinje cells.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, and as shown in Fig. 60.6, electromicrographic analyses of the zones of termination of granule cell synapses on Purkinje cell dendrites have shown that synapses of the ascending segment of the axon are restricted to only the smallest diameter dendrites, whereas parallel fiber synapses are concentrated on the larger diameter spiny dendrites (GundappaSulur et al 1999;Lu et al 2009). Accordingly, to effect the soma, the influence of ascending segment synapses must traverse regions of the Purkinje cell dendrite under direct voltage control of parallel fiber excitation and molecular layer inhibition.…”
Section: Functional and Algorithmic Implications For The Cerebellar Mmentioning
confidence: 97%
“…With further experimental evidence suggesting that ascending synapses made numerous direct Purkinje cell contacts (Gundappa-Sulur et al 1999;Lu et al 2009;Mugnaini 1972) and had large physiological effects (Jaeger and Bower 1994;Lu et al 2005), the next question addressed using the realistic models was the lack of parallel fiber effects after granule cell layer activation. Exploring this question required that the single Purkinje cell model be embedded into a cortical network model (Santamaria et al 2007).…”
Section: Uncovering Function From Structurementioning
confidence: 99%
“…Anatomical differences in the distributions of granule cell axons and their synapses [73][74][75] are likely to be functionally quite important in determining selectivity and effectiveness across Purkinje cells. Knowledge of how individual mossy fiber terminals distribute not only with respect to cerebellar zones, but also with respect to depth within the granular layer is certainly relevant.…”
Section: Molecular Layer Inhibitory Interneuronsmentioning
confidence: 99%